SEBLAK APPLICATION "NEWS ABOUT THE ACCIDENT" ANDROID BASED - Ahmad Nurul Fiqri; Sita Anggraeni; Nabila Zen; Riri Anisah Azmmi (Jurnal Techno Nusa Mandiri, 2019)
The SEBLAK application "Regarding Accident News" based on android is present to provide news and information validly to the families of victims, with the use of features in the application that contain clear information. The stage of making the application starts from the preparation of the data needed and used tools Unified Modeling Language (UML) in designing diagrams such as ERD, Usecase, Activity Diagram up to Sequence Diagrams, then designing or designing systems and applications, implementation and testing applications. Hopefully with this application the victim's family will get valid information about the accident that befell the victim. Of course this application is very helpful in finding information on families of victims who have had accidents in South Jakarta in particular